Bacteriocin Production by Strains of Bacteroides Isolated from Human Feces and the Role of These Strains in the Bacterial Ecology of the Colon - Booth, S. J. (1977)
Several human fecal isolates of Bacteroides have been found to produce bacteriocins. The bacteriocin-producing strain T1-1 was studied in the most detail. Strain T1-1 belongs to the 0061-1 deoxyribonucleic acid (DNA) homology group of Bacteroides. This homology group phenotypically resembles Bacteroides thetaiotaomicron but has little DNA homology with it. The bacteriocin-producing strains T1-12 and T1-48 belong to the 3452-A DNA homology group. This group has DNA homology with B. thetaiotaomicron and Bacteroides ovatus. The bacteriocin-producing strain T1-42 remains unidentified in that it does not belong to any recognized DNA homology group of the saccharolytic intestinal bacteroides. The extracellular bacteriocin produced by strain T1-1 was specifically bactericidal for other bacteria within the genus Bacteroides. The highest bacteriocin titers (32 to 64) were produced in complex media, with only trace amounts being produced in a defined medium. The bacteriocin appeared to have a high molecular weight (≥300,000) and was unusual because it was stable from pH 1 to 12 and only a 50% reduction in activity resulted after 15 min at 121°C in an autoclave. It was inactivated by trypsin and Pronase. Strain T1-1 was isolated from all three fecal samples obtained over a 25-week period from an individual who was part of a National Aeronautics and Space Administration mock Skylab flight. Strains T1-12, T1-48, and T1-42 were isolated only from the first fecal sample. Each of these strains was immune to the bacteriocins produced by the others. These strains were found to coexist in the colon with a larger population of non-bacteriocin-producing, bacteriocin-susceptible strains of Bacteroides.